Wirausaha Pemula: Latar Belakang Keluarga Pengusaha Versus Non Pengusaha - Gultom, Jonathan; Indriyo, Wahyu; Hartono, Dang Arif; Dhammananda, Arisandi (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
This study seeks to analyze the performance and key supporting factors of novice entrepreneurs with and without a family business background. A descriptive quantitative approach was employed, utilizing purposive sampling to select 100 respondents from each group of novice entrepreneurs. The data were analyzed using descriptive analysis and the Mann-Whitney t-test. The findings reveal significant differences in business performance and supporting factors between novice entrepreneurs from entrepreneurial families and those from non-entrepreneurial backgrounds.